La fiebre aftosa en América del Sur - Goié M., Roberto (Avances en Ciencias Veterinarias, 1989)
In this general article it is presented the situation of foot-and-mouth disease in South América from the first outbreak occurred in 1870 in Buenos Aires, Argentina. The control of this disease is discussed in relation to the strategic criteria of the South American Commission for the Control of Foot–and–mouth disease, with special emphasis on support and concern at governmental levels. Palabras claves: fiebre aftosa, virus aftoso, bovinosKey words: foot-and-mouth disease.